Detrital zircon U–Pb dating and Hf isotope study of late Palaeozoic sedimentary rocks in central–eastern Jilin Province, NE China: Constraints for tectonic evolution of the eastern segment of the Paleo‐Asian Ocean. (24th June 2019) - Shi, Chenglong; Ding, Xiaozhong; Liu, Yanxue; Zhou, Xiaodong
Abstract : This paper reports in situ U–Pb ages and Hf isotopic data on detrital zircons from Palaeozoic strata in central‐eastern Jilin Province, NE China, with the aim of constraining the timing of final closure of the Paleo‐Asian Ocean and the tectonic evolution of the eastern segment of the Central Asian Orogenic Belt (CAOB). Zircons from Middle to Late Permian Fanjiatun and Yangjiagou formations in central Jilin Province are characterized by four major groups of age populations (2.5–2.3 Ga, 1.9–1.7 Ga, 1.3–1.0 Ga, and Late Palaeozoic ages). The Paleo‐Mesoproterozoic and Cambrian zircons have positive εHf (t) values, suggesting that the source was mainly locally derived from the CAOB, whereas a lesser amount of Archean zircons with positive εHf (t) values, indicating that source from the North China Craton (NCC). The Phanerozoic zircons have both positive and negative εHf (t) values indicates that material from bidirectional provenances in the CAOB and the NCC. However, Late Permian Kaishantun Formation in eastern Jilin Province contain a single group of Phanerozoic zircons with positive εHf (t) values, distinct from known igneous zircons in the NCC, suggesting a local source. These observations, along with the results of previous studies on Middle–Late Permian igneous rocks in Jilin Province, indicate that the eastern segment of the Paleo‐Asian Ocean underwent the initial closure in central Jilin Province during the Middle Permian and the final closure in eastern Jilin Province in the Late Permian–Early Triassic. The detrital zircon geochronological data clearly record two stages of tectonic evolution and the scissor‐like closure model of the Paleo‐Asian Ocean in the eastern segment of the CAOB.